Land Fictions The Commodification of Land in City and Country - Balakrishnan, Sai; Christophers, Brett; Dwyer, Michael B.; Ferring, David; Ghertner, D. Asher; Ghertner, D. Asher; Harms, Erik; Hausermann, Heidi; Knuth, Sarah; Lake, Robert W.; Lake, Robert W.; Levien, Michael; et al. (Cornell Series on Land: New Perspectives on Territory, Development, and Environment, 2021)
Land Fictions explores the common storylines, narratives, and tales of social betterment that justify and enact land as commodity. It interrogates global patterns of property formation, the dispossessions property markets enact, and the popular movements to halt the growing waves of evictions and land grabs.This collection brings together original research on urban, rural, and peri-urban India; rapidly urbanizing China and Southeast Asia; resource expropriation in Africa and Latin America; and the neoliberal urban landscapes of North America and Europe. Through a variety of perspectives, Land Fictions finds resonances between local stories of land's fictional powers and global visions of landed property's imagined power to automatically create value and advance national development. Editors D. Asher Ghertner and Robert W. Lake unpack dynamics of land commodification across a broad range of political, spatial, and temporal settings, exposing its simultaneously contingent and collective nature. The essays advance understanding of the politics of land while also contributing to current debates on the intersections of local and global, urban and rural, and general and particular